A functional form-stable phase change composite with high efficiency electro-to-thermal energy conversion. (15th March 2017) - Wu, Wenhao; Huang, Xinyu; Li, Kai; Yao, Ruimin; Chen, Renjie; Zou, Ruqiang
Graphical abstract: The thermal conductivity of PU was enhanced to 43 times of the pristine value by encapsulation in a PGF, PU@PGF can be used for highly efficient electro-to-heat energy conversion and storage with the highest energy storage efficiency up to 85%. Highlights: The composite exhibits an in-situ solid-solid phase change behavior. The enthalpy of polyurethane is enhanced within the matrix. The thermal conductivity of the composite is 43 times as much as that of the polyurethane. Supercooling of polyurethane is greatly reduced. The composite is applied to cold protection as a wear layer. Abstract: A novel solid-to-solid phase change composite brick was prepared by combination of polyurethane (PU) and pitch-based graphite foam (PGF). The carbonaceous support, which can be used for mass production, not only greatly improves the thermal conductivity but promote electro-to-heat conversion efficiency of organic phase change materials (PCMs). Our composite retained the enthalpy of PCM and exhibited a greatly reduced supercooling temperature. The novel composite was investigated by differential scanning calorimetry (DSC), thermogravimetric analysis (TGA) and scanning electron microscope (SEM). The enthalpy of polyurethane has increased about 8.6% after infiltrating into graphite foam. The composite was very stable during thermal cycle test, and the electro-to-heat conversion efficiency achieves to 85% at lower voltages (1.5–1.8 V), which can vastly reduce energy consumption. The as-prepared composite was used in a wear layer to test its performance comparing with normal fabric.